2005
DOI: 10.1088/1742-5468/2005/01/p01011
|View full text |Cite
|
Sign up to set email alerts
|

Response of a hexagonal granular packing under a localized external force: exact results

Abstract: Abstract. -We study the response of a two-dimensional hexagonal packing of rigid, frictionless spherical grains due to a vertically downward point force on a single grain at the top layer. We use a statistical approach, where each configuration of the contact forces is equally likely. We show that this problem is equivalent to a correlated q-model. We find that the response displays two peaks which lie precisely on the downward lattice directions emanating from the point of application of the force. With incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…From all these data, as in 2D, we conclude the existence of a macroscopic anisotropy induced by the pile preparation. Similar conclusion could be drawn for 3D response functions experiments [28,29] or simulations and calculations performed on highly symmetrical crystalline packing [13,30,31,32,33].…”
Section: Three-dimensional Experimentssupporting
confidence: 81%
“…From all these data, as in 2D, we conclude the existence of a macroscopic anisotropy induced by the pile preparation. Similar conclusion could be drawn for 3D response functions experiments [28,29] or simulations and calculations performed on highly symmetrical crystalline packing [13,30,31,32,33].…”
Section: Three-dimensional Experimentssupporting
confidence: 81%
“…Following a similar path, we studied the response of a two-dimensional hexagonal packing of rigid, frictionless spherical grains (see Fig. 1) to a pointlike external force F , and found that it is concentrated mainly on the two lattice directions emanating from the point of application of the force (Ostojic & Panja 2005), in agreement with experiments (Geng 2001). Our definition of the response of the packing is…”
Section: Introductionsupporting
confidence: 74%
“…Nevertheless, one has to be careful: notice that the G i,j 's are differences of the physical contact forces and thus they are allowed to become negative in magnitude. In < F 0 appear elsewhere [18,19]) This arrangement reduces the uniform measure over E to the uniform measure on S ′ , which is a (N + 1)p-dimensional polyhedron.…”
mentioning
confidence: 99%
“…In Refs. [26,27], we examined this packing under zero vertical and large horizontal pressure. While this situation allows an instructive comparison between the force ensemble and the q-model [28], physically it corresponds to a singular limit, where there is no relevant scale for the applied overload [30].…”
mentioning
confidence: 99%